Productive diagnosis of Girolando cows on a farm in Alto Sertão Sergipano - Silva, L. R. A.; Castelo Branco, P. A.; Barreto, L. M. G.; Vale, W. G.; Brêtas, A. A.; Souza, M. B. (Scientific Electronic Archives, 2020)
Girolando breed has several blood grades, from 1/4 Dutch (Hol) x 3/4 Gir (G), to 7/8 Hol x 1/8 G. These animals have good milk production characteristics inherited from the Dutch breed and a good acquired rusticity of the Gir breed. In view of this, this work aimed to evaluate the productive performance of three different blood grades of the Girolando breed on a farm in the Alto Sertão Sergipano. For the research, the data used referred to the highest production in 305 days of distinct lactations, between the first and the fourth lactation. The blood grades evaluated were: 1/2 HG (G1); 3/4 HG (G2) and 7/8 HG (G3). For the diagnosis, the Individual Control Chart was used, which is one of the tools of the Statistical Process Control (SPC), with the purpose of evaluating and controlling, in a global way, all the production. The results obtained do not demonstrate superiority of production among the three genetic groups. However, the G1 group showed the highest regularity in milk production, with the highest average production and the lowest average range. However, in order to obtain a better diagnosis of milk production, more studies are needed addressing milk production in 305 days with different blood grades of the Girolando breed, in the Alto Sertão Sergipano region. Â